The Utilisation of Audiovisual Media in Akidah Akhlak Subject to Improve Student Learning Outcomes - Moh. Fahril; Muhammad Djamil M Nur; Riska Elfira (JIE (Journal of Islamic Education), 2026)
This study aims to examine the forms of audiovisual media utilisation in the Akidah Akhlak subject and analyse student learning outcomes at MIs Karya Thayyibah Limran Pantoloan Boya. The research employs a qualitative case study design to explore the implementation of audiovisual media in depth and context. Data collection was conducted through participatory observation, in-depth interviews with teachers, school principals, and students, and documentation of learning materials and student achievement data. Data analysis utilised the interactive model of Miles, Huberman, and Saldana, encompassing data condensation, data display, and conclusion drawing. Data validity was ensured through triangulation of techniques and sources, member checking, and thick description. The findings reveal that audiovisual media are systematically utilised through animated learning videos, interactive multimedia presentations, and documentary films, integrated with active learning strategies such as viewing guides, group discussions, and creative project assignments. This implementation is supported by adequate technological infrastructure, continuously developed teacher competencies, and ongoing evaluation. Student learning outcomes demonstrate documented improvements across three domains: cognitive aspects, evidenced by increased average scores and mastery percentages; affective aspects, marked by enhanced motivation and positive attitude changes; and psychomotor aspects, reflected in the development of digital literacy, social skills, and noble character formation. This research employs a qualitative approach, supported by quantitative data, to explore these improvements. The novelty of this study lies in its contextual, process-oriented exploration within a madrasah ibtidaiyah setting in Central Sulawesi — a region underrepresented in the existing literature, which experimental-quantitative designs have dominated. This research contributes to achieving SDG 4 by documenting evidence of learning technology's effectiveness in improving the quality of Islamic religious education and preparing generations who are intellectually and spiritually intelligent, as well as competent in facing digital-era challenges.